Kontribusi Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Di Provinsi Papua Periode 2014-2021 - Yahya Nusa; Ludia Panggalo (Journal of Financial and Tax, 2022)
This research aims to analyze the influence of the contribution of regional taxes and regional levies on regional original income in the province of Papua period 2014-2021. This research uses multiple linear analysis tools. The results of the research show that separately, regional taxes have a positive and significant effect on regional original income, while regional levies have a positive and insignificant effect on regional original income. And the simulation shows that regional taxes and regional levies have a positive and significant effect on regional original income in the province of Papua period 2014-2021.